1992
DOI: 10.1139/b92-280
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, pigments, and chloroplast ultrastructure of an Antarctic liverwort from sun-exposed and shaded sites

Abstract: POST, A., and VESK, M. 1992. Photosynthesis, pigments, and chloroplast ultrastructure of an Antarctic liverwort from sun-exposed and shaded sites. Can. J. Bot. 70: 2259-2264. Adaptations to severe environmental conditions were studied in the only recorded continental Antarctic hepatic, Cephaloziella exiliflora (Tayl.) Steph. During the summer growing season Antarctic plants melt out and many are exposed fully to the sun. C. exiliflora plants collected from sun-exposed and shaded sites were compared. Most plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 16 publications
3
48
0
Order By: Relevance
“…During this period we also recorded a rise in chlorophyll a / b ratio from 1.45 to 2.46, the same value as that recorded by Post and Vesk (1992). This is analogous to the response recorded by Martin and Churchill (1982), who found that chlorophyll a / b ratio declined in a range of mosses after canopy closure in a temperate forest.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…During this period we also recorded a rise in chlorophyll a / b ratio from 1.45 to 2.46, the same value as that recorded by Post and Vesk (1992). This is analogous to the response recorded by Martin and Churchill (1982), who found that chlorophyll a / b ratio declined in a range of mosses after canopy closure in a temperate forest.…”
Section: Discussionsupporting
confidence: 88%
“…Similar effects of UV-B radiation on the accumulation of anthocyanins in plant tissues are well documented (Chalker-Scott, 1999). Furthermore, our study indicates that the reduced chlorophyll concentrations in sun-exposed C. varians tissues reported by Post and Vesk (1992) are also most probably owing to UV-B radiation exposure. After 35 d, chlorophyll concentrations in tissues of plants exposed to reduced UV-B were almost twice those of tissues exposed to high doses of UV-B.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations